(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the reality of knowledge management implementation in higher education institutions and to uncover the obstacles affecting it. The study adopted the descriptive-analytical approach, which is considered appropriate for it. The study sample consisted of (43) employees from the organization under study. A questionnaire was designed and distributed to the target sample. Statistical methods appropriate to the study were used. The study concluded with a number of results, the most important of which are: that the level of implementation of knowledge management processes in higher education institutions was at the average level; that there is a weakness in the culture of knowledge sharing within the institution, which is a crucial factor in explaining the limited level of implementation; that there is a weakness in information and communication technologies; that there is a weakness in the infrastructure supporting knowledge management; that there is also a weakness in incentives; and that there is a lack of systematic documentation of employees’ experiences. The study also showed a clear explanatory relationship between the level of implementation and the obstacles; as the high level of awareness of the obstacles was accompanied by the level of implementation remaining at the average level, which indicates that the obstacles represent structural determinants that directly affect the effectiveness of knowledge management implementation within higher education institutions.